Endoscopic debridement for non-insertional Achilles tendinopathy with and without platelet-rich plasma - Hajo Thermann; Ralph Fischer; Nikolaos Gougoulias; Lucio Cipollaro; Nicola Maffulli (Elsevier, 2023)
Background: When non-operative management fails to improve symptoms in patients with non-insertional Achilles tendinopathy, surgery may be required. Various open and endoscopic techniques have been proposed, and platelet-rich plasma (PRP) injections have been proposed as an adjunct to aid tendon healing. Methods: Thirty-six patients with mid-portion Achilles tendinopathy were randomized to undergo endoscopic debridement alone (n = 19) or in combination with intraoperative PRP application (n = 17). Clinical outcome measures included the Visual Analogue Scale for pain, function, and satisfaction and the Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire. Patients were followed-up at 6 weeks, 3 months, 6 months, and 12 months after surgery. An MRI examination at 3 and 12 months was used to assess signal alterations within the tendon. Results: Both groups showed significant clinical improvement (p < 0.05) after surgery, with no difference between the 2 groups. Tendon diameter increased at 3 months and decreased at 12 months. The tendinopathy area increased at 3 months and decreased at 12 months below baseline level in both groups. There was no significant difference between the groups regarding the MRI parameters. Nodular thickening and MRI-detected signal alteration persisted after surgery, with no association between imaging and clinical outcome. Five minor complications were reported: 2 in the PRP group and 3 in the control group. Conclusion: Endoscopic debridement of the Achilles tendon improved clinical outcomes in patients with mid-portion tendinopathy. The addition of PRP did not improve outcomes compared to debridement alone. MRI parameters showed no association with clinical outcomes.